The Effect of Ambient Air Pollution on Severity of COVID19: Hospitalisation and Death - Yari, Saeed; Moshammer, Hanns (Asian Pacific Journal of Environment and Cancer, 2020)
The advent of a new Corona virus, SARS-CoVi-2, causing COVID-19, which first began in Wuhan, China, and then spread worldwide, has created a global public health crisis [1]. The sudden and far-reaching pandemic has raised many immediate questions. A very important goal of public health is to identify environmental factors that affect the spread and severity of the disease. Air pollution is one of the most well-known causes of long-term inflammation, which ultimately leads to increased immune system hyperactivity [2]. Air pollution is one of the leading causes of death and is estimated to play a role in nearly 5 million premature deaths worldwide in 2017 alone. Numerous scientific studies have linked air pollution to a variety of health concerns, including premature death in patients with heart or lung disease, non-fatal heart attacks, irregular heartbeats, and severe asthma [3].